PENGARUH MACAM BAKTERI DEKOMPOSER PADA MEDIA PENGOMPOSAN YANG BERBEDA DENGAN PEMBANDING BAKTERI SUBTILIS TERHADAP HASIL KOMPOS - Aziez, Achmad Fatchul; Budiyono, Agus; Sari, Siti Mardhika; Ameylia, Annisa Dika (Universitas Islam Kadiri, 2025)
Bacteria play a role in processing agricultural waste into compost. Rice and corn straw waste has potential as organic fertilizer. This research aims to compare the effectiveness of decomposer bacteria in the composting process. The research was carried out in Bowan, Klaten, February-June 2023, using a completely randomized factorial design consisting of 8 treatments and 4 replications. The first factor is the type of bacteria consisting of no bacteria, cellulotic+rhizomonas, cellulotic+BRS, rhizomonas+subtilis, subtilis, while the second factor is the type of composting media, namely straw and corn. Observations include water hold capacity, time, weight and compost water content. The results of the research show that the type of bacteria influences the water hold capacity, time and weight of the compost. In the composting process, corn waste is more effective than straw. The interaction of the type of bacteria and composting media influences the water holding capacity, time and weight of the compost. In conclusion, subtilis bacteria play an important role in accelerating composting, increasing efficiency through the correct interaction of bacteria and waste. Corn waste is superior to straw in producing high quality compost.